PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER), NET PROFIT MARGIN (NPM), TOTAL ASSETS TURN OVER (TATO), dan SIZE TERHADAP PERUBAHAN LABA - Anggita Diah Lestari; Mohamad Zulman Hakim (Universitas Muhammadiyah Tangerang, 2019)
Penelitian ini bertujuan untuk mengetahui pengaruh rasio lancar, rasio hutang terhadap ekuitas, margin laba bersih, total perputaran aset dan ukuran perusahaan pada perubahan laba sektor perdagangan. Terdapat 32 sampel data industri perdagangan yang terdaftar di Bursa Efek Indonesia pada periode 2016-2019 diperoleh dengan menggunakan teknik purposive sampling. Teknik menganalisis data yang menggunakan regresi linier berganda bahwa rasio lancar, rasio hutang, dan margin laba bersih berpengaruh signifikan terhadap perubahan laba dan total perputaran aset dan ukuran perusahaan tidak berpengaruh signifikan terhadap perubahan laba pada sektor industri perdagangan. Rasio saat ini, rasio utang terhadap ekuitas, margin laba bersih, total perputaran aset dan ukuran perusahaan mempengaruhi perubahan laba bersamaan dengan perubahan industri perdagangan.Kata Kunci: current ratio, debt to equity ratio, net profit margin, total assets turn over, size. AbstractThis reasearch aims to determine the effect of current ratio, debt to equity ratio, net profit margin, total asset turnover and company size on changes in profit in the trading sector. There are 32 samples of trade industry data listed on the Indonesia Stock Exchange in 2016-2019 period were obtained using purposive sampling technique. The technique of analyzing data uses multiple linear regression that shows that current ratios, debt ratios, and net profit margins have a significant effect on changes in earnings and total asset turnover and company size has no significant effect on changes in earnings in the trading industry sector. The current ratio, debt to equity ratio, net profit margin, total asset turnover and company size all influence changes in earnings along with changes in the trading industry.The Abstract should be informative and completely self-explanatory, provide a clear statement of the problem, the proposed approach or solution, and point out major findings and conclusions. The Abstract should be 100 to 150 words in length. The abstract should be written in the past tense. Standard nomenclature should be used and abbreviations should be avoided. No literature should be cited. The keyword list provides the opportunity to add keywords, used by the indexing and abstracting services, in addition to those already present in the title. Judicious use of keywords may increase the ease with which interested parties can locate our article.Keywords: current ratio, debt to equity ratio, net profit margin, total assets turn over, size.